Environmental Physics Program: An Evaluation and Reconstruction - Santo Nurso; Supriyadi (International Journal of Science and Society, 2019)
Higher education faces major challenges in the interruption era. Universities in the Indonesian Ministry of Science, Technology and Higher Education are encouraged to revive the curriculum in accordance with the Indonesian National Qualifications Framework (INQF). However, this is considered to be lacking. Every argument that comes from recovery must be changed. Therefore, it is necessary to evaluate and reconstruct the course. Reconstruction is an improvement on a course based on the need to review its relevance to everyday needs. The purpose of this study is to evaluate and reconstruct the themes of environmental physics. Based on the assessment of PGRI Semarang University Physics Environmental Physics courses, it is concluded that learning and learning methods need to be modified by adapting requirements. The result of the reconstruction of environmental physics is the integration of ethane technology into teaching materials and methods. This integration will help students better understand the physical concepts of companies and their impact on the environment